Incidence and mortality due to thromboembolic events during the COVID-19 pandemic: Multi-sourced population-based health records cohort study. Issue 202 (June 2021) - Aktaa, Suleman; Wu, Jianhua; Nadarajah, Ramesh; Rashid, Muhammad; de Belder, Mark; Deanfield, John; Mamas, Mamas A.; Gale, Chris P.
Abstract: Background: Evidence supports an excess of deaths during the COVID-19 pandemic. We report the incidence and mortality of thrombo-embolic events (TE) during the COVID-19 pandemic. Methods: Multi-sourced nationwide cohort study of adults (age ≥18 years) admitted to hospital with TE and deaths from TE in England (hospital and community) between 1st February 2018 and 31st July 2020. Relative risks, adjusted for age, sex, atrial fibrillation, co-morbidities and time trend comparing before and during the COVID-19 pandemic were estimated using Poisson regression. Findings: Of 272, 423 patients admitted with TE to 195 hospitals, 86, 577 (31.8%) were admitted after 2nd March 2020 (first COVID-19 death in the UK). The incidence of TE hospitalised increased during the COVID-19 pandemic from 1090 to 1590 per 100, 000 (absolute risk change 45.9% [95% CI 45.1–46.6%], adjusted relative risk [ARR] 1.43 [95% CI 1.41–1.44]) driven particularly by pulmonary embolism; 1.49, 95% CI 1.46–1.52. TE were more frequent among those with COVID-19; 1.9% vs. 1.6%, absolute risk change 21.7%, 95% CI 21.0–22.4%, ARR 1.20, 95% CI 1.18–1.22. There was an increase in the overall mortality from TE during the pandemic (617, 6.7% proportional increase compared with the historical baseline), with more TE deaths occurring in the community compared with the historical rate (44% vs. 33%). Interpretation: The COVID-19 pandemic has resulted in an increase in the incidence of hospitalised TE. There were more deaths from TE in the community highlighting a number of mechanisms including the hypercoagulable state associated with COVID-19 infection and potential impact of delays in seeking help. Research in context: Evidence before this study We searched PubMed on 16 November 2020 for articles that documented the incidence and mortality of thrombo-embolic events (TE) during the COVID-19 pandemic using the search terms "COVID-19" OR "Coronavirus*" OR "2019-nCOV" OR "SARS-CoV" AND ("Thromboembolism" OR "Venous Thromboembolism" OR "thromboembol*") with no language or time restrictions. The majority of data on TE in COVID-19 pertains to hospitalised patients from retrospective cohort studies. One study found that TE in hospitalised patients was associated with an increased mortality rate (adjusted hazard ratio 1.82; 95% CI 1.54–2.15). A systematic review and meta-analysis of 35 studies in 9249 hospitalised patients calculated an overall pooled incidence of TE of 17.8% (95% CI: 9.9–27.4%), rising to 22.9% (95% CI: 14.5–32.4%) in patients admitted to intensive care (ICU). The most contemporary data are from a cohort of 1114 patients (715 outpatient, 399 hospitalised, 170 admitted to ICU). With robust COVID-19-specific therapies and widespread thromboprophylaxis the prevalence of venous TE in ICU patients was reported as 7% ( n  = 12) when catheter-/device-related events were excluded, and among the outpatients there was no TE reported. No published studies have used nationwide data to investigate TE during the pandemic or the effect of the pandemic on outcomes of patients with TE but without Covid-19. Added value of this study This retrospective multi-sourced nationwide unlinked cohort study compares the overall incidence and mortality of TE prior to and during the COVID-19 pandemic. We found an increased incidence of TE despite only a small proportion having a diagnosis of COVID-19. This may highlight the lack of testing, particularly in the community during the initial phase of the pandemic, and the possibility of other factors contributing to TE risk, such as decreased daily activity mandated by home quarantine and alterations in medication concordance. Mortality from TE was higher in the community during the pandemic and this highlights that adverse societal effects of the pandemic, such as aversion to seeking medical assessment, may precipitate worse outcomes related to TE. Implications of all the available evidence Evidence suggests that COVID-19 produces a hypercoagulable state and thromboprophylaxis is recommended in hospitalised patients to prevent excess mortality from TE. Whether to anticoagulate non-hospitalised ambulatory patients with COVID-19 will be answered by ongoing trials. Clinicians should consider the risks posed by decreased daily activity and fear of medical contact, and provide appropriate advice to patients. Graphical abstract: Unlabelled Image Highlights: Thrombo-embolic event (TE) have been described as one of the major cardiovascular complications of COVID-19. The incidence of TE hospitalised increased during the COVID-19 pandemic. The increase was driven particularly by pulmonary embolism. TE were more frequent among those with COVID-19. More TE deaths occurred in the community during the COVID-19 pandemic compared with the previous years.